Ultrafast lateral 600 V silicon SOI PiN diode with geometric traps for preventing waveform oscillation. (February 2015) - Tsukuda, Masanori; Imaki, Hironori; Omura, Ichiro
Highlights: It was found that there was a large potential for faster reverse recovery between the state-of-the-art commercialized diode and the theoretical limit. The potential reverse recovery speed was much higher than that of the state-of-the-art diode and was almost the same as the commercialized SiC-SBD. We proposed a completely different diode, namely the lateral silicon-on insulator diode with geometric traps. It has convexo-concave-shaped traps with Si and oxide on top of the buried oxide. Abstract: An ultrafast lateral silicon PiN diode with geometric traps is proposed using a silicon-on-insulator (SOI) substrate with the traps. The proposed diode successfully suppresses waveform oscillation because the trapped hole suppresses electric field penetration and prevents the oscillation trigger known as "dynamic punch-through." Because of the short current path caused by the oscillation prevention, the reverse recovery speed was higher and the reverse recovery loss was strongly reduced. The proposed trap structure and design method would contribute to performance improvement of all power semiconductor devices including IGBTs and power MOSFETs.